2018
DOI: 10.1038/sdata.2018.268
|View full text |Cite
|
Sign up to set email alerts
|

Overview and experience of the YODA Project with clinical trial data sharing after 5 years

Abstract: The Yale University Open Data Access (YODA) Project has facilitated access to clinical trial data since 2013. The purpose of this article is to provide an overview of the Project, describe key decisions that were made when establishing data sharing policies, and suggest how our experience and the experiences of our first two data generator partners, Medtronic, Inc. and Johnson & Johnson, can be used to enhance other ongoing or future initiatives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
74
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(76 citation statements)
references
References 36 publications
(26 reference statements)
1
74
0
1
Order By: Relevance
“…21 The YODA project is one example of data sharing that has pooled clinical trial data since 2013 and facilitated secondary use of the database. 28 While data from industrysupported clinical trials can provide a rich substrate from which to conduct secondary analyses, their utility and generalizability may be less robust with respect to older patients who are often excluded from these studies because of their age or because they have medical conditions and/or are prescribed medications for these conditions.…”
Section: How Will Decisions About How the Data Are Used Be Made?mentioning
confidence: 99%
“…21 The YODA project is one example of data sharing that has pooled clinical trial data since 2013 and facilitated secondary use of the database. 28 While data from industrysupported clinical trials can provide a rich substrate from which to conduct secondary analyses, their utility and generalizability may be less robust with respect to older patients who are often excluded from these studies because of their age or because they have medical conditions and/or are prescribed medications for these conditions.…”
Section: How Will Decisions About How the Data Are Used Be Made?mentioning
confidence: 99%
“…https://doi.org/10.1101/19000463 doi: medRxiv preprint Similarly, Supporting Open Access to Research (SOAR), a partnership between Bristol-Myer Squibb (BMS) and Duke Clinical Research Institute, provides access to BMS trial data. 48 There are also university-based platforms, included the Yale Open Data Access (YODA) project, which has partnered with Johnson & Johnson, Medtronic, Inc., and SI-BONE, Inc. 24,49,50 Not only do these platforms ensure that all shared data are deidentified, they also require requestors to pre-specify their research questions and methods. Furthermore, they employ a "trusted intermediary" approach, with independent review committees screening detailed proposals and making data-sharing decisions.…”
Section: Data Sharing Implicationsmentioning
confidence: 99%
“…This term refers to the distribution of individual participant-level clinical trial data to other researchers to enable independent use for scientific purposes. 16 Over recent years, the importance of sharing data from clinical trials has substantially grown and several major organizations and institutions have developed policies and recommendations to promote the development of data sharing. 17 However, data sharing is a very complex enterprise, both legally and logistically.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, a major logistical problems associated with data sharing is a lack of complete infrastructure to suport sharing data on a global scale. 18 Therefore, despite many benefits of data sharing and a wide promotion of this idea, 16,17 the access of investigators to individual participant-level datasets remains rather limited. For instance, a recent study showed that only 15% of clinical trials sponsored by pharmaceutical industry were available for data sharing 2 years after publication of primary results.…”
Section: Introductionmentioning
confidence: 99%